IMPLEMENTASI SUPERVISI KEPALA SEKOLAH DALAM PEMBELAJARAN DEEP LEARNING ANAK USIA DINI - Zahara, Siti; Kurnia, Rita; Sabna Putri Nainggolan, Aisyah; Azzahra, Mutiara; Ramadhana, Nabila; Zenidah, Salsabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the principal's supervision and management inimplementing the deep learning approach at the UPT TK Negeri Pembina 01 Salo.This study closely observed several purposefully selected principals. This studyused interviews and documents to collect information. Then, all data was carefullyanalyzed by sorting it, displaying it clearly, and drawing conclusions based on theexisting findings. The results of the study indicate that academic supervision iscarried out through RPPH planning tailored to child characteristics, implementationof exploration-based learning and simple projects, and reflection as a follow-up tolearning improvements. From a managerial aspect, the principal supports theimplementation of deep learning by providing learning facilities, teacher training, anda holistic assessment system that covers cognitive, social-emotional, and characteraspects. In general, the principal's supervision and management have supportedthe creation of meaningful and child-centered learning, although there are stillchallenges in terms of differences in child abilities and parental support.